Application of local electric spark deposition technology - Srebrov, Bozhidar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Local electric spark deposition technology in the paper is presented. The scheme of the method and his optimization is examined. The applications of this technology by means ELFA machines are described.